Realising a species-selective double well with multiple-radiofrequency-dressed potentials - Barker, AJ; Sunami, S; Garrick, D; Beregi, A; Luksch, K; Bentine, E; Foot, CJ (IOP Publishing, 2020)
Techniques to manipulate the individual constituents of an ultracold mixture are key to investigating impurity physics. In this work, we confine a mixture of hyperfine ground states of 87Rb atoms in a double-well potential. The potential is produced by dressing the atoms with multiple radiofrequencies. The amplitude and phase of each frequency component of the dressing field are controlled to independently manipulate each species. Furthermore, we verify that our mixture of hyperfine states is collisionally stable, with no observable inelastic loss.